The Impact of Consumption Behaviour on Farm Investment among Rural Farmers in Anambra State, Nigeria - M.O , Ugbaja; Chidebelu , S.A.N.D (African Journal of Education,Science and Technology (AJEST), 2013)
The study investigated the impact of consumption behaviour on farm investment among rural farmers in Anambra State, Nigeria. Specifically, it sought to describe the socio-economic characteristics of the respondents, examine the effect of these characteristics on farm investment and expenditure pattern of the farmers and sustainable agricultural and rural development. Multistage and simple random sampling methods were used to select 144 respondents. Primary data were collected by means of questionnaire and analysed by use of non-parametric and parametric statistical tools, including percentages, frequency distribution and Binary logistic regression analysis. Majority (96.5%) of the farmers were married, 89% were literate, 73% had above 11 years of experience in farming, 76.4% obtained between N 75,000 and N 160,000 as annual income, while 73% of them spend between N 80,000 and N 120,000 annually. Consumption expenditure was significantly influenced by marital status, educational level, dependency ratio, farm income and technology acquisition. Increased farm investment for sustainable agriculture and rural transformation and development would be ensured by acquisition of technology, extension of birth control education, provision of micro credits and engagement in off farm activities to supplement income from farming.